3D-QSAR Study of 2-Morpholinochromones as Selective Phosphodiesterase-2 Inhibitors - K. Goel, Pradeep; K. Jatav, Rakesh; Kawathekar, N. (Asian Journal of Chemistry, 2010)
Three-dimensional quantitative structure activity relationship study on series of 2-morpholinochromones with phosphodiesterase-2 inhibitory activity was performed using a combination of various thermodynamic, electronic and spatial descriptors. Several statistical regression expressions were obtained using sequential multiple linear regression analysis. The best QSAR model (r > 0.80, Fischer test value = 8.45, S < 0.37, change correlation < 0.001) have acceptable statistical quality and predictive potential as indicated by the value of cross-validated squared correlation coefficient (Q2 > 0.43). Thermodynamic parameters (standard Gibb's free energy, stretch energy) and electronic parameters (dipole moment, HOMO energy) were found to have significant correlation with biological activity.